Investigation of carbon dioxide foam performance utilizing different additives for fracturing unconventional shales - Ahmed, S. (Society of Petroleum Engineers, 2019)
The application of CO2 foam has caught overwhelming attention for fracturing shales. In applications, high foam deterioration and insufficient viscosity at operating conditions are the major concerns associated with foam fracturing process. In this study, polymer-free CO2 foam possessing high stability has been presented through chemical screening and optimization under HPHT conditions. Initial screening was performed by conducting a series of foam stability experiments considering different commercial anionic surfactants, concentration, and foam stabilizer addition using FoamScan instrument. Foam rheology study was then performed by considering the similar investigated factors under fracturing conditions using HTHP foam rheometer. All the tested solutions were prepared in fixed brine salinity and HPAM polymers with different molecular weights were used in evaluation of the performance of the designed polymer-free foam in term of foam strength. In comparison with other types of surfactant, alpha olefin sulfonate (AOS) exhibited the best foam stability and viscosity at testing conditions. The optimum AOS concentration providing the best performance was found to be 5000 ppm and its combination with 5000 ppm of foam booster (betaine) further increased AOS foam longevity. An improved result on foam stability and viscosity was not obtained by increasing surfactant concentration. Results on foam rheology reveals that CO2 foam generated in the presence of different molecular weight classical HPAM polymers could not provide significant increment in foam viscosity under experimental conditions. It was observed that these types of polymer underwent degradation due to some unfavorable mechanisms which will be expected to negatively affect its performance during fracturing process. On the other hand, polymer-free CO2 foam was found to produce a higher stability and relatively equally high viscosity compared to polymer-stabilied CO2 foam without experiencing degradation at high pressure and temperature conditions. Therefore, based on this study, it is recommended to use polymer-free foam for fracturing shales application. The use of formulated polymer-free CO2 foam which has high stability and viscosity will lead to improved fracture cleanup, minimized formation damage and pore plugging, and efficient proppant placement which will ultimately enhance gas recovery from unconventional shales. Â© 2019, Society of Petroleum Engineers